Conceptual blending across ontological domains: references to time and space in motion events by Tunisian Arabic speakers of L2 German - Gerwien, Johannes; Stutterheim, Christiane von (Frontiers in communication, 2022)
Patterns of information selection and verbal encoding may rely on an interdependence between the spatial and temporal conceptual domain in the context of motion events. This has been shown, e.g., for Tunisian Arabic (TA), a language with a highly differentiated aspectual system. We address the question whether this interdependence can also be observed when L1 speakers of TA describe motion events in their L2 German, a language without grammaticalized aspect. Data obtained in an unscripted language production experiment in which L1 and highly advanced L2 speakers of German describe videos showing different types of motion events (one type showing boundary crossing at a goal like a woman entering a supermarket, the other type showing motion along a path with no evident goal such as a car driving along a road) suggest that this is indeed the case. The L2 speakers deviate systematically from the L1 speakers of German in the information they select for verbal encoding, but show clearly similar patterns to those used when describing the same scenes in the L1 (TA). The differences can be interpreted as pointing to the high relevance attributed to the temporal dimension of the events shown in the videos by the L2 speakers. The results are placed in the theoretical framework of schema theory. The findings for Arabic speakers of L2 German can be explained by assuming that the same event schema is activated in the context of L2 use as in the context of L1 use.
Gesehen am 13.04.2022